The effects of COVID-19 on the health and socio-economic security of sex workers in Nairobi, Kenya: Emerging intersections with HIV. Issue 7 (2nd July 2020) - Kimani, Joshua; Adhiambo, Joyce; Kasiba, Rosemary; Mwangi, Peninah; Were, Veronica; Mathenge, John; Macharia, Pascal; Cholette, Francois; Moore, Samantha; Shaw, Souradet; Becker, Marissa; Musyoki, Helgar; et al.
ABSTRACT: The COVID-19 pandemic, and its attendant responses, has led to massive health, social, and economic challenges on a global scale. While, so far, having a relatively low burden of COVID-19 infection, it is the response in lower- and middle- income countries that has had particularly dire consequences for impoverished populations such as sex workers, many of whom rely on regular income in the informal economic sector to survive. This commentary captures the challenges in Kenya posed by daily curfews and lost economic income, coupled with further changes to sex work that increase potential exposure to infection, stigmatisation, violence, and various health concerns. It also highlights the ways in which communities and programmes have demonstrated resourcefulness in responding to this unprecedented disruption in order to emerge healthy when COVID-19, and the measures to contain it, subside.